Third-harmonic generation via nonlinear Raman-Nath diffraction in nonlinear photonic crystal - Sheng, Yan; Wang, Wenjie; Shiloh, Roy; Roppo, Vito; Arie, Ady; Krolikowski, Wieslaw (Optics Letters, 2011)
We report on the observation of multiple third-harmonic conical waves generated in an annular periodically poled nonlinear photonic crystal. We show that the conical beams are formed as a result of the cascading effect involving two parametric processes that satisfy either the transverse and/or longitudinal phase-patching conditions. This is the first experimental observation of third-harmonic generation based on nonlinear Raman-Nath diffraction. © 2011 Optical Society of America.
Created from Fastlane, Scopus look-up